Cediranib Induces Apoptosis, G1 Phase Cell Cycle Arrest, and Autophagy in Non-Small-Cell Lung Cancer Cell A549 In Vitro. (30th March 2021) - Guo, Menghuan; Liu, Zhiyuan; Si, Jing; Zhang, Jinhua; Zhao, Jin; Guo, Zhong; Xie, Yi; Zhang, Hong; Gan, Lu
Abstract : Lung cancer remains the leading cause of cancer death worldwide. Late diagnosis, chemoresistance, and metastasis are the main reasons for the high mortality rate of lung cancer. Therefore, the development of other treatments is urgent. Cediranib (CED), a vascular endothelial growth factor receptor (VEGFR) kinase inhibitor, shows promising antitumour activities in various cancers including lung cancer. Here, we explored the effects and the underlying molecular mechanism of CED on non-small-cell lung cancer (NSCLC) cell line A549 cells in vitro. Our results show that CED could inhibit A549 cell proliferation and cloning formation. Meanwhile, G1 phase cell cycle arrest was also found, as featured by the increased proportion of G1 phase cells as well as the reduction of G1 phase relative proteins CDK4/cyclin D1 and CDK2/cyclin E. Moreover, the ratio of LC3-II/LC3-I was elevated significantly in CED-treated groups compared with the controls. Furthermore, the expression of p-Akt, p-P38, p-Erk1/2, and p-mTOR proteins was decreased obviously in the treatment groups. These results suggest that CED could induce apoptosis and G1 phase cell cycle arrest in A549 cells. Meanwhile, CED may induce autophagy through MAPK/Erk1/2 and Akt/mTOR signal pathway in A549 cells.